Multicultural Performance in the Linguistic Landscape of Sampit City, Central Kalimantan, Indonesia (Anthropolinguistic Study) - Erma Lestari; Kisyani Laksono; Syamsul Sodiq (Journal of Language Development and Linguistics, 2026)
This study examines multicultural performance in the culinary linguistic landscape in Sampit City using Landry and Bourhis's linguistic landscape theory framework and Duranti's anthropolinguistics concept of performativity. Studies on linguistic landscapes generally focus on representational and symbolic functions, while the performative role of language in constructing multicultural realities remains underexplored, especially in a multicultural context. This study uses a descriptive mixed-methods approach through visual ethnography, and simple data qualification in the form of public culinary texts such as business names, menus, and signboards collected in 2025. The results show that language in the culinary linguistic landscape functions performatively through four main dimensions, namely representing cultural identity, becoming